Studi Hadits Tentang Perceraian Karena Bahaya Penyakit Menular Dalam Kasus HIV/AIDS - Abu Yazid Adnan Quthny; Kottrunnada Sofia (FIQHUL HADITS : Jurnal Kajian Hadits dan Hukum Islam, 2025)
This study examines the phenomenon of divorce caused by infectious diseases from the perspective of the Prophet’s hadith, with particular attention to cases of HIV/AIDS that continue to increase in society. This issue is significant because it concerns the safety of spouses within marriage and how Islamic teachings provide solutions when potential harm arises in marital relationships. The purpose of this study is to explore the normative foundations found in the Prophet’s hadiths that allow divorce under certain circumstances to prevent greater harm. This research employs a descriptive qualitative method using a library research approach. Data were collected through the examination of relevant literature, including classical and contemporary hadith compilations, fiqh books, and other scholarly works related to divorce and infectious diseases. The analysis focuses on hadiths related to the prevention of harm in marital life, such as the narration concerning the Prophet’s divorce from a woman of Bani Ghifar and the hadith “lā ḍarar wa lā ḍirār” (there should be neither harm nor reciprocating harm), which serves as an important principle in Islamic law. The findings indicate that the Prophet’s hadiths provide a normative basis for preventing harm within marriage. In certain situations, divorce can be considered a legitimate solution when a marital relationship poses a significant threat to the safety of one of the spouses. Thus, the teachings of the Prophet not only emphasize the importance of maintaining marital harmony but also offer guidance when the protection of life and welfare becomes a primary consideration.